Professional learning communities in early childhood in Chile - Guerra, Paula (2020)
An alternative for teacher professional development is Professional Learning Communities (PLC), a space highly valued and supported by evidence. An area rarely addressed are the contextual and institutional factors associated with PLCs. In order to investigate them, two PLCs composed of early childhood teachers were analyzed. Through a case study, teachers and institutional representatives were interviewed, as a group and individually. The findings highlight management, process coordination, vision and strategic planning as relevant aspects, along with reflective processes that accompany the evolution of PLCs. The convergences and divergences of both cases are discussed, as well as the theoretical and practical implications.